2019
DOI: 10.1182/bloodadvances.2018028043
|View full text |Cite
|
Sign up to set email alerts
|

Health outcomes and services in children with sickle cell trait, sickle cell anemia, and normal hemoglobin

Abstract: The health effects of sickle cell trait among children are unknown. We compared select health outcomes and health services utilization among children with sickle cell trait, sickle cell anemia (SCA), and normal hemoglobin. Newborn screening records were used to identify children with sickle cell trait and SCA born in Michigan (1997-2014) who were enrolled in Michigan Medicaid for ≥1 year from 2012 to 2014. Each select health outcome (acute otitis media, acute respiratory infections, fever, invasive pneumococca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…This is consistent with sickle cell trait being largely an asymptomatic disease. [16][17][18] After matching on age, sex, and other known comorbidities, there were no significant differences between the 2 groups. It is noteworthy that in our sickle cell trait cohort, the majority were female, most likely because they are tested for trait at the time of their obstetrics/gynecology care.…”
Section: Discussionmentioning
confidence: 88%
“…This is consistent with sickle cell trait being largely an asymptomatic disease. [16][17][18] After matching on age, sex, and other known comorbidities, there were no significant differences between the 2 groups. It is noteworthy that in our sickle cell trait cohort, the majority were female, most likely because they are tested for trait at the time of their obstetrics/gynecology care.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have also reported associations between carrier status for CFTR and CF-associated symptoms. 20 In contrast, SCA carriers had slightly lower risk of pneumonia and influenza (OR = 0.93) compared to subjects with normal hemoglobin, 22 although pneumonia severity was not studied. We applied Fisher’s exact test to investigate the effect of the risk allele in heterozygous carriers of the risk allele compared to those homozygous for the reference allele.…”
Section: Main Textmentioning
confidence: 99%
“… 21 Children with SCA are more likely to have pneumonia and influenza (OR = 7.38) and acute respiratory infections (OR = 1.29). 22 Acute chest syndrome (ACS) is a common complication of SCD and can be triggered by pneumonia and vaso-occlusive crises and is the leading cause of death in individuals with SCA. 23 Clinically differentiating between ACS and pneumonia can be difficult, and they often overlap in the EHR.…”
Section: Main Textmentioning
confidence: 99%
“…Throughout the COVID-19 pandemic, patients with SCD were thought of as "high risk" due to impaired immunity, resulting from hyposplenism and systemic vasculopathy, which gives them the tendency for endorgan dysfunction and high risk for thrombosis [5,7]. In addition, previous studies have reported their vulnerability to acute viral illnesses [8] and subsequent exacerbation of vaso-occlusive crises and acute chest syndromes [9].…”
Section: Introductionmentioning
confidence: 99%